Fund Effectiveness School Operational Assistance at State Vocational Schools in the Province Central Sulawesi Republic of Indonesia - M, Rudin. (Journal of Ecohumanism, 2025)
The purpose of this study is (1) to find out and analyze the effectiveness of the use of operational assistance funds for state vocational schools in Central Sulawesi Province , Republic of Indonesia. (2) to find out and analyze inhibiting factors in The effectiveness of the implementation of Operational Assistance Funds for State Vocational High Schools in Central Sulawesi Province , Republic of Indonesia. This type of research is qualitative research . Data collection using observation, interview and documentation techniques. The data analysis technique used is effectiveness analysis . Based on the results of research and analysis carried out by the researcher, it was concluded that (1 ) Use of Operational Assistance Funds for State Vocational Schools in Central Sulawesi Province, Republic of Indonesia. is in the effective criteria . This is because the effectiveness value is at 100 percent. (2) Inhibiting factors in the Use of Operational Assistance Funds for State Vocational Schools in Central Sulawesi Province , Republic of Indonesia. that is Socialization of training (b ) Human Resources Facilities and Infrastructure, (c) financial administration (d) Fund distribution. ( 3) Supporting Factors in the Use of Operational Assistance Funds for State Vocational Schools in Central Sulawesi Province , Republic of Indonesia. namely a clear Legal Basis (b) Clear Funding Flow (c) Employee Loyalty (e) Good Data and Information . Keywords: Effectiveness, Funds, Operations and Schools.